INVESTIGATING CHALLENGES, OPPORTUNITIES AND SOLUTION OF ENTREPRENEURIAL EDUCATION IN SHAPING FUTURE ENTREPRENEURS - Prathivi, Maria Dini Gilang; Dewobroto, Wisnu Sakti; Adi, Antonius; Windawaty, Herry; Widhoyoko, Samuel Anindyo; Agustian, Sanggup Leonard (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Entrepreneurship is one of the key pillars in achieving the success of the Sustainable Development Goals (SDGs) by alleviating poverty and bridging educational disparities. One crucial aspect in fostering entrepreneurship is the role of education. The current situation and competition require entrepreneurs who are adaptable and capable of addressing market needs, thereby creating added value. Entrepreneurship education faces several challenges, including insufficient facilities, the need to enhance educators' attitudes and competencies, and the lack of effective coordination and allocation of resources. This study aims to explore best practices in entrepreneurship education to enhance the quality of entrepreneurship graduates. The research was conducted using a qualitative approach, with data collected through Focus Group Discussions involving experts in entrepreneurship education. The findings of this study reveal challenges in entrepreneurship education, such as inadequate educational infrastructure, insufficiently competent teaching staff, and an inadequate curriculum. The proposed solutions include training programs to enhance educators' competencies, providing adequate infrastructure, and developing a curriculum that is practically oriented to meet the demands of the digital era.